Dermoscopic Features of Subcorneal Hematoma on the Palms and Soles: Differences from Acral Melanoma - Won, Sang-Hyeon; Seong, Jeongwu; Lee, Jungsoo; Shin, Kihyuk; Kim, Hoon-Soo; Ko, Hyun- Chang; Kim, Byung-Soo; Kim, Moon-Bum (Archives of Clinical and Biomedical Research, 2023)
Purpose: The diagnosis of subcorneal hematoma (SH) can be challenging because the clinical presentation of SH can resemble melanocytic lesions. Few studies have examined the characteristic dermoscopic features of SH, but a more detailed large-scale study is needed to overcome the diagnostic challenge of differentiating it from acral melanoma. Materials and Methods: We evaluated the clinical and dermoscopic features of 50 SH lesions from 43 patients at the Pusan National University Hospitals (Busan and Yangsan). Results: In the color analysis, 86% of cases showed the bruise color sign; 7 cases had a single color (red to purple: 2; black: 1; brown: 4). Typical dermoscopic features of SH, acral nevi, and acral melanoma-associated patterns were observed in 60%, 0%, and 72% of lesions, respectively. Hematoma-associated patterns were homogenously red to black with or without satellite globules (32%) and pebbles on the ridges (28%). Acral melanoma-associated patterns showed a parallel ridge pattern (PRP) (52%), irregular dots and globules (50%), polychromia (34%), asymmetry (24%), irregular blotches (10%), and ulcers (10%). No case showed bluewhite veils, regression structures, atypical vascular patterns, or irregular fibrillar patterns. The bruise color sign was positive in most cases with acral melanoma-associated patterns (88.9%). Conclusion: This study revealed the positive (bruise color sign, distinct PRP, and polychromia) and negative (blue-white veil, regression structures, atypical vascular pattern, and irregular fibrillar pattern) dermoscopic features of SH. Cases that are ambiguous between SH and acral melanoma can be distinguished based on these features.